2011
DOI: 10.1097/igc.0b013e3181ffbed8
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Human Papillomavirus-Related Lesions on Quality of Life: A Multicenter Hospital-Based Study of Women in Mainland China

Abstract: Women with GWs and precancerous cervical lesions had the worst psychological burden, and sexual-related concern was the primary cause of burdens regarding HPV-related diseases for Chinese women. In addition to basic medical treatments, psychosocial support systems should be established, and consultation services should be generalized to help alleviate these burdens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
37
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 15 publications
(19 reference statements)
5
37
0
Order By: Relevance
“…These results are in line with other studies that report that anxiety is common in patients with abnormal test results and can exceed a period of 6-34 months after Pap smear test has been taken [2,11,16]. Abnormal test results are associated with a negative psychological impact, lead to a psychological burden and cause a highly distressing condition [10,17,29]. Some patients associate an abnormal Pap smear with an early Data from questions 10, 12, 13, 15 * Scale from 1 to 10, where 1 is no effect and 10 is severely affected ** Scale from 1 to 10, where 1 is not at all informed and 10 is very well informed *** Multiple responses possible **** Two responses possible Arch Gynecol Obstet stage of cervical cancer [23] and therefore the severity of anxiety seems to be dependent from knowledge about the disease [17,20].…”
Section: Discussionsupporting
confidence: 94%
“…These results are in line with other studies that report that anxiety is common in patients with abnormal test results and can exceed a period of 6-34 months after Pap smear test has been taken [2,11,16]. Abnormal test results are associated with a negative psychological impact, lead to a psychological burden and cause a highly distressing condition [10,17,29]. Some patients associate an abnormal Pap smear with an early Data from questions 10, 12, 13, 15 * Scale from 1 to 10, where 1 is no effect and 10 is severely affected ** Scale from 1 to 10, where 1 is not at all informed and 10 is very well informed *** Multiple responses possible **** Two responses possible Arch Gynecol Obstet stage of cervical cancer [23] and therefore the severity of anxiety seems to be dependent from knowledge about the disease [17,20].…”
Section: Discussionsupporting
confidence: 94%
“…Also in the Taiwanese study by Wang et al ,29 receipt of a positive HPV test after abnormal cytology had a similar psychological impact as a histologically confirmed CIN diagnosis. In contrast, the large Chinese study by Wang et al 31 reported that a histological CIN diagnosis had a significantly worse psychosocial impact compared to a diagnosis of an abnormal smear.…”
Section: Resultsmentioning
confidence: 86%
“…This was the case for distress and state anger in a study by Palmer et al ,17 anxiety about cervical cancer in a study by Salz et al ,30 and ‘psychosocial impact’ (combining, for example, worry about future health and fertility, depression, anxiety, sexual and partnership problems, deterioration of self-image, effect on sleep) in studies by Mast et al 28 in the USA, Pirotta et al 27 in Australia, Wang et al 31 in China and Wang et al 29 in Taiwan. Measured with the latter instrument, the psychosocial impact of a CIN diagnosis was less negative than that of EGW in the two studies undertaken in Chinese-speaking populations and in the US study 28 29 31. In the Australian study, no differences were found for psychosocial impact and quality of life between women with CIN2/3 and women with EGW 27…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies demonstrated that GW was associated with a significant detriment to health-related Quality of life (QoL), but the origins of these psychosocial burdens were still unclear [4-7]. Recently, literature reported that female patients with GW underwent a significantly heavier psychosocial burden than the general population in China [5,8]. This national study highlighted the psychosocial burden of Chinese women with GW, inciting interest in exploring the afflictions of a different group with extremely high incidence, Chinese male GW patients, as well as variations between sexes.…”
Section: Introductionmentioning
confidence: 99%